Defining Service Quality of BRI Merchant Application Using Importance Performance Analysis - Permana, Ardi Rizky; Sudhartio, Lily (Jurnal EMT KITA, 2024)
The COVID-19 pandemic has changed people's habits worldwide, accelerating the adoption of cashless payment transactions, especially in Indonesia. This situation allows Financial Technology companies and Conventional Banks to increase competition. This thesis focuses on the Digital Payments Industry in Indonesia, emphasizing the Merchant Acceptance Business, which has a crucial role as a catalyst for Cashless Payments. This research is based on previous studies regarding service quality, business model canvas, and the importance of performance analysis of the BRI Merchant Application. This research aims to define a service quality strategy for BRI merchant applications through a critical performance analysis approach. The study found that the quality of BRI merchant application services consists of changing merchant data, adding EDC, Checking transactions, reconciling Payments, filing complaints, and monitoring complaints.